PENGARUH VARIABEL MAKRO TERHADAP IHSG DI BURSA EFEK INDONESIA - Isworo, Sri; Luhur, Suryo (Universitas Muhammadiyah Magelang, 2010)
The purpose of this study to investigate : whatare money circulation, deposit interest, inflation and exchange rate simultaneously influence to the Jakarta Composite Index, what are money circulation, deposit interest, inflation and exchange rate partially influence to the Jakarta Composite Index and which of the money circulation, deposit interest, iflation and exhange rate dominantly influence to the Jakarta Composite Index. This study using Partial Adjustment Models (PAM) as analysis tools. This study fouds : money circulation, deposit interest, infltion and exchange rate simutaneously influence significantly to the composite stock index but deposit interest and inflation not significant influence to the Jakarta Composie Index and money circulation dominantly influence to the Jakarta Composite Index.